The Effect of Multipass Strategy on Students’ Reading Comprehension at Senior High School Level - JAILANI, AHMAD (J-SHMIC : Journal of English for Academic, 2018)
Being able to read in English is very important. Success in reading is the most necessary because it is a basic tool of education. Based on the syllabus of Islamic Senior high School Hidayatul Mubtadiin (MAHM), it is hoped that students should comprehend monolog texts in narrative, spoof and hortatory exposition forms well. After doing preliminary observation at MAHM, some of the students of the second year still had low ability in their reading comprehension. The dominant factors influencing their low reading comprehension are the lack of vocabulary and teaching strategy of reading comprehension. From the two of dominant factors, the researcher is interested to investigate about teaching reading comprehension. Thus, the researcher conducted a research on the effect of Multipass strategy on Reading comprehension. This research investigates students’ reading comprehension taught by using multipass strategy at MAHM Siak Sri Inderapura. The design of this study was Quasi-experimental research by post-test only. The subject of this research was the second year students of MAHM. The total population was 42 students, and the sample was 42 students. Data were collected by using a test. Then, the data were analyzed by using t-test formula. It was found that there was a significant effect of using multi pass strategy on students’ reading comprehension at MAHM.